Intermediates and Bimolecular Structures Formed through Thermal and Tip-Induced Partial Dehydrogenation of 2,2,2-Trifluoro-1-phenylethanol on Pt(111) - Zeng, Yang; Dong, Yi; Zhang, Xueqin; Yin, Xiuli; Tuai, Tim; Groves, Michael N.; McBreen, Peter H. (Journal of physical chemistry. C, 2022)
Dimerization, thermal and tip-induced partial dehydrogenation, and surface dynamics of 2,2,2-trifluoro-1-phenylethanol (TFPE) on Pt(111) were investigated in relation to the enantioselective hydrogenation of 2,2,2-trifluoroacetophenone (TFAP). Measurements were made on racemic and (R)-TFPE and compared to data for TFAP. The structures of homochiral and minority heterochiral TFPE dimers, formed using racemic TFPE, were determined from combined RAIRS, STM, and DFT data, revealing homochiral Z-structures rather than the linear-type dimers predicted by DFT. Interconversion between homochiral Z-structures and buckled heterochiral dimers was observed and is attributed to the transient formation of termolecular structures. While thermally driven partial dehydrogenation was observed at approximately 270 K, tip-induced dissociation of dimers through partial dehydrogenation was observed at 220–240 K. Time-lapsed STM measurements at different temperatures revealed a dimer dissociation process that we attribute to the tip-induced formation of alkoxy-TFAP followed by surface diffusion. The migration of the newly formed alkoxy species leads to the formation of relatively immobile monomers and hydroxy-TFAP/TFAP structures at undetermined sites distant from the parent dimer. Both tip-induced O–H bond scission and thermal C*-H bond scission pathways convert TFPE to hydroxy-TFAP/TFAP structures, the same structures that are formed through partial hydrogenation of TFAP on Pt(111) above 240 K. In the context of the hydrogenation of TFAP on chirally modified Pt, formation of stable hydroxy-TFAP/TFAP structures may reduce the enantiomeric excess obtained in that they compete with the formation of the modifier–substrate complexes required for chirality transfer and in that they may also induce carbonyl function activation through hydrogen bonding. However, we provide spectroscopic evidence that TFAP in model TFAP/1-(1-naphthyl)ethylamine/Pt(111) diastereomeric complexes is subject to stronger activation of the carbonyl bond.